Lanthanopolyoxotungstoborates: synthesis, characterization, and layer-by-layer assembly of europium photoluminescent nanostructured films - Sousa, FL (2004)
New lanthanopolyoxotungstoborates, K6 xHx[Ln(BW11O39)(H2O)3] nH2O, Ln(III) Sm, Eu, Tb, Er, were prepared and characterized by spectroscopic methods (Fourier transform infrared, Fourier transform-Raman, 11B solid-state nuclear magnetic resonance, and photoluminescence) and elemental analysis. A layer-by-layer assembly method was employed to fabricate multilayered films containing the europium heteropolyanion and the polyelectrolytes poly(sodium 4-styrenesulfonate) and poly(diallydimethylammonium chloride). The photoluminescence behavior of these final nanostructures was inv